Bertrand Tavernier's Coup de torchon - Thompson, Jim 1906-1977; Sarde, Philippe 1945-; Thompson, Jim 1906-1977 (Criterion, 2001)
After Lucien Cordier, the only police officer in a small African village, is ridiculed by the local pimp, cheated on by his wife, and suffers his mistresses being beaten, he begins to get rid of the evil ones in his life.
Bildformat 1.66:1 (16:9) aspect ratio, widescreen
Orig.: Frankreich 1981
Enth. exclusive video interview with Bertrand Tavernier ; an alternate ending
Keywords: Administrateurs coloniaux - L'Afrique - Drame; Colonial administrators -- Africa -- Drama; Man-woman relationships -- Drama; Murder -- Drama; Afrika; Feature films